Sustainable prayer chair design characteristic for people with disabilities / Badwin Shah Zawawi ... [et al.] - Zawawi, Badwin Shah; Hazim, Zulkarnain; Haron, Siti Sazlina; Ayob, Salwa (2022)
Muslims need to fulfil their duty by performing solah five times a day that is compulsory. However, people with disabilities face some difficulties due to loss or changes in their body structural functionality. Praying in a chair could be a beneficial option for individuals that could not go for years. Less attention is given to the uncomfortable congregation when performing solah, which is a significant concern to all Muslims during prayers. For this reason, this paper focuses study on the characteristic of sustainable prayer chair design for people with disabilities. Data were drawn from the available literature on solah, disability, sustainability, and usability, anthropometric and ergonomics, and aspects of furniture design. Data were analysed through the content analysis method. The results were a composition of understanding the requirement and characteristics of the sustainable prayer chair design for disabilities in terms of functional and aesthetic and the expectations for the environment. Consequently, the components that contribute to the standard appearances and usefulness of the physical user were reviewed and discussed. The findings provide a structural understanding of functional versus aesthetic characteristics of prayer chair design.